2021
DOI: 10.1016/j.cjtee.2020.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study to compare the treatment outcomes with and without surgical navigation for fracture of the orbital wall

Abstract: Purpose To evaluate the outcomes with and without aid of a computer-assisted surgical navigation system (CASNS) for treatment of unilateral orbital wall fracture (OWF). Methods Patients who came to our hospital for repairing unilateral traumatic OWF from 2014 to 2017 were included in this study. The patients were divided into the navigation group who accepted orbital wall reconstruction aided by CASNS and the conventional group. We evaluated the surgical precision in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…[16][17][18] The medial wall is the site where orbital fractures are prone to occur, and the purpose of surgical treatment is to restore the anatomical part of the eyeball, remove the incarceration of orbital contents and repair the orbital wall fracture, and most views believe that the best time for surgery is 2 weeks after injury, not more than 3-4 weeks after injury. 19,20 Traditional medial orbital wall reconstruction surgery mostly uses transconjunctival and transcutaneous approach, 13,14 and although operation time of the transcutaneous incision is short, it often leaves an obvious scar on the face, and there is a risk of damaging the lacrimal sac or the medial canthal ligament, causing eyelid misalignment. The advantage of conjunctive incision is that it can quickly reach the orbital wall of the fracture, and the risk of optic nerve injury is minimized, but it has the disadvantages of insufficient exposure of the surgical field and difficulty in fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] The medial wall is the site where orbital fractures are prone to occur, and the purpose of surgical treatment is to restore the anatomical part of the eyeball, remove the incarceration of orbital contents and repair the orbital wall fracture, and most views believe that the best time for surgery is 2 weeks after injury, not more than 3-4 weeks after injury. 19,20 Traditional medial orbital wall reconstruction surgery mostly uses transconjunctival and transcutaneous approach, 13,14 and although operation time of the transcutaneous incision is short, it often leaves an obvious scar on the face, and there is a risk of damaging the lacrimal sac or the medial canthal ligament, causing eyelid misalignment. The advantage of conjunctive incision is that it can quickly reach the orbital wall of the fracture, and the risk of optic nerve injury is minimized, but it has the disadvantages of insufficient exposure of the surgical field and difficulty in fracture fixation.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intraoperative navigation has been shown to offer a significantly better orbital volume and eyeball projection, without increasing surgery duration. 23 Customized titanium implants accurately reproduce orbital contours thus restoring orbital volume. This reduces operative time and improves the functional and aesthetic outcomes of post-traumatic orbital reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…The use of intraoperative navigation has been shown to offer a significantly better orbital volume and eyeball projection, without increasing surgery duration. 23…”
Section: Discussionmentioning
confidence: 99%
“…DNS allows reorientation of the fracture with immediate evaluation of fracture reduction by superimposing preoperatively planned positioning and intraoperatively acquired images (Soh et al 2022). Its successful implementation has been observed across zygomatic complex fractures (Gong et al 2017), orbital wall fractures (Zong et al 2021), and mandibular, condylar, and multiple maxillofacial fractures (Wang, Chi, et al 2022). DNS in orbital reconstruction exemplifies computer-assisted surgery and personalized medicine.…”
Section: Dns In the Repair Of Maxillofacial Fracturesmentioning
confidence: 99%
“…It enables a more accurate implementation of preoperative plans for fracture reduction, guides the surgeon during the exploration of an orbital fracture, and directs the proper placement of an orbital implant, thereby yielding substantial improvements in the postoperative bilateral symmetry of the orbital region (Soh et al 2022). A retrospective study comparing DNS with FH for orbital wall fractures showed that DNS provides better surgical precision, enhanced orbital-cavity volume, improved eyeball projection, and superior clinical outcomes without prolonging surgery time (Zong et al 2021). Currently, one limitation of DNS is the inability to mirror the unaffected side during bilateral operations.…”
Section: Dns In the Repair Of Maxillofacial Fracturesmentioning
confidence: 99%